Modification and Application of Waste Rubber Powder - Ding, G.X.; Yang, J.N.; Duan, W.H. (Asian Journal of Chemistry, 2013)
The surface of waste rubber powder was modified by maleic anhydride and styrene via an ultraviolet treatment. Modified waste rubber powder/natural rubber composites were prepared. Modified waste rubber powder were characterized by scanning electron microscope and thermogravimetric analysis. The effects of content of modified waste rubber powder and mass ratio of styrene-maleic anhydride on tensile strength of composites were investigated. The results show that maleic anhydride and styrene have been successfully grafted onto the surface of waste rubber powder. Better compatibility between modified waste rubber powder and natural rubber is responsible for the enhancement of tensile strength of composites.